EVALUATION AND SERVICE IMPROVEMENT OF PASSENGER FACILITIES AT THE NORTH GATE OF BANDUNG STATION - Gabriela Palupi, Adriana
Bandung Station is the largest type A station in West Java which facilitates the movement of passengers from the city of Bandung. The trend of increasing number of passengers from year to year has certainly affected the services of several passenger facilities, especially facilities that are affected by the number of passengers. This can be seen in the poor circulation of vehicles in parking area and passenger circulation in boarding area during peak hours. For this reason, it is necessary to carry out an evaluation so that suggestions for improving passenger service facilities at the north gate of Bandung Station can be given up to the year of 2033 which is planned using the multiple linear regression method. Evaluation of passenger facility services will be carried out by collecting primary and secondary data. Primary data was obtained through survey activities or observation and distributing questionnaires to the train passengers traveling long distances from Bandung Station, while secondary data was obtained directly from related agencies. In this study, the evaluation of passenger facility services includes passenger facilities inside and outside the station building. Passenger facilities inside the station building consist of passenger facilities contained in the Minimum Service Standards for the Transport of People by Train at Railway Stations in the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 63 of 2019, while passenger facilities outside the station building consist of parking facilities and vehicle stops for general passengers. The results of the evaluation show that there are still passenger facilities at the station that do not meet the Minimum Service Standards and need to be improved by installing guiding blocks on the platform area, providing procedures for buying train tickets, installing a map of the train network in non-ticketed areas, equipping toilets with urinals for children, and a prayer room with seats for users with special needs. The boarding area itself still meets the Minimum Service Standards because each passenger has space freedom of 1,659 m2/person with LOS A. In addition, there are also passenger facilities outside the station building that need to be improved by improving parking inventories and suggesting the construction of bus stops and public transportation at a separate location. Improving passenger service facilities outside the station building is also carried out by designing parking layouts and circulation with a capacity of 180 SRP for cars and 4 SRP for users with special needs. The overall service improvement of passenger facilities is budgeted to cost Rp3.976.455.038,48.